Prednisolone as an Effective Treatment for Epilepsy - F. İlik; A.C. Pazarli; A. Dogan (European Journal of Inflammation, 2014)
Rasmussen encephalitis is a chronic inflammatory disease commonly seen in children. Hemispheric atrophy, intellectual disability, and hemiparesis are characteristics of this rare disease. The main pathological findings are chronic meningeal and parenchymal inflammation attributed to T lymphocytes. Plasmapheresis, immunomodulators, and immunosuppressives are commonly used for treatment. In this article, a patient suffering from Rasmussen encephalitis whose seizures were treated with prednisolone is discussed according to the literature.